Variability of physical parameters in Sabah and Sarawak waters due to the southwest monson - Lim Phaik Kin (Terengganu: Universiti Putra Malaysia Terengganu, 2014)
This study provides new information on the physical characteristics of water masses in Sabah and Sarawak waters. The aim is to determine the effect of Southwest monsoon on the variability of water masses, in Sabah and Sarawak waters. Data were obtained using an iCTD System, during the third (July 1996) and fourth (May 1997) cruises of MV SEAFDEC research vessel, under SEAFDEC collaborative research program in the South China Sea between Malaysia and Thailand.